THE ROLE OF BIOCHEMISTRY IN THE SOLUTION OF SOME MEDICAL AND BIOLOGICAL PROBLEMS - Knyazyeva, Maryna (European Science, 2023)
Understanding the basic patterns of metabolism in the human body allows not only to prevent errors in the diagnosis of diseases, to develop the correct treatment strategy, but also to participate in the solution of some medical and biological problems.T